An empirical study on the characterization of machined surface integrity by chip morphology in dry end-milling of titanium alloy. (March 2014) - Arif, Muhammad; Rahman, Mustafizur; San, Wong Yoke; Kumar, Senthil
Titanium alloys manifest low thermal conductivity and high work hardenability in machining. These alloys are thus considered as difficult-to-machine at higher cutting speeds and pose serious problems in machining such as degraded machined surface and rapid tool-wear. Mostly, the integrity of the machined surface is assessed by post-process microscopic examination or by metallurgical testing techniques where machined workpiece needs to be further processed to perform subsequent testing on sophisticated equipment in usually meticulous ways. This study presents a qualitative but simple approach for the rapid characterization of the machined surface integrity in high-speed milling of titanium alloy. It has been established empirically that the chip morphology carries significant information about the machined surface integrity, and hence, can be considered as a reliable representative of the machined surface integrity.